1993
DOI: 10.1021/jo00070a016
|View full text |Cite
|
Sign up to set email alerts
|

An approach to total synthesis of (+)-lycoricidine

Abstract: A convergent synthesis of a protected version of (+)-lycoricidine has been accomplished in 13 steps from L-arabinose. Preparation of the aminocyclitol moiety 50 employed a novel vinylsilane-terminated N-sulfonyliminium ion cyclization of vinylsilane aldehyde 42. Closure of the B-ring using an intramolecular Heck reaction afforded lycoricidine derivative 58. An unexpected cyclization of vinylsilane aldehyde 42 allowed for the stereodivergent preparation of semiprotected conduritols 43 and 45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 0 publications
1
45
0
1
Order By: Relevance
“…Mp: 102e103 C (Lit. 19 (s,3H),4.20 (q,J ¼ 7.4 Hz,1H), 5.23 (d,J ¼ 7.4 Hz,1H),7.02 (m,2H),7.11 (d,J ¼ 8.1 Hz,2H),7.15 (m,3H),7.56 (d,J ¼ 8.2 Hz,2H). 13 C NMR (CDCl 3 , 75 MHz): d (ppm) 10.6, 21.5, 30.7, 59.9, 126.7 (2C), 127.1 (2C), 127.…”
Section: N-(1-phenylpropyl)-tosylamide (15)mentioning
confidence: 99%
“…Mp: 102e103 C (Lit. 19 (s,3H),4.20 (q,J ¼ 7.4 Hz,1H), 5.23 (d,J ¼ 7.4 Hz,1H),7.02 (m,2H),7.11 (d,J ¼ 8.1 Hz,2H),7.15 (m,3H),7.56 (d,J ¼ 8.2 Hz,2H). 13 C NMR (CDCl 3 , 75 MHz): d (ppm) 10.6, 21.5, 30.7, 59.9, 126.7 (2C), 127.1 (2C), 127.…”
Section: N-(1-phenylpropyl)-tosylamide (15)mentioning
confidence: 99%
“…with reaction times from 30 min to 22 h, [54][55][56][57][58][59][60][61][62][63] whereas in other cases the same reaction was reported to take place in less than one hour at -78°C. [64,65] This suggested two alternative pathways: one fast, taking place even at -78°C, and another one slow, going through the phosphorane 52 (Scheme 7). Two papers seemed particularly interesting to us: Bestmann reported that better yields could be obtained by addition of CBr 4 to the mixture of aldehyde and PPh 3 , [66] whereas Weinreb, in his total synthesis of licoricidin, [64] faced a situation similar to ours -under the classical conditions (high temperature) only aldehyde decomposition was observed, whereas, upon mixing all three reagents at -78°C, a very fast reaction (only 5 min) gave the expected product in good yields.…”
Section: Resultsmentioning
confidence: 99%
“…427 [190,[514][515][516] (+)-Lycoricidine One of the most remarkable applications is the one reported for the construction of the skeleton of taxol (402) [574] by an 8-exo-trig cyclization of the enol triflate 400 [301a,b] (Scheme 8.79). The ring closure of the eight-membered ring to complete the rigid and compact tricyclic system is not trivial [145].…”
Section: Syntheses Of Heterocycles Natural Products and Other Biolomentioning
confidence: 99%